Morphological genetic markers for selection of broiler lines - Schmidt,GS (2003)
Two paternal broiler lines (LL and LLc, originated from the same stock in 1998) of Embrapa Suinos e Aves genetic program were used. Line LL had been selected for eight generations for rapid growth while LLc had been mated randomly, without selection, as a control line. In the last generation, 30 males and 240 females were used in hierarchical matings with pedigree control to determine sire effect. The same number of birds were used, but matings were at random for LLc. Eggs of both lines were incubated and embryos were collected in different development stages (40, 45, 50, 55 and 60 hours after setting) in order to determine somite number (NOS). The number of evaluated embryos were 1,967 and 498 for LL and LLc, respectively. This study aimed to determine the changes in somite formation during embryonic development that resulted from artificial selection for heavier body weight. In the evaluated generation, the differences for body weight, feed conversion ratio, carcass and breast yields between LL and LLc were 546 g; 0.16 FC units, 2.20 and 2.19%, respectively. NOS was greater in the initial (40 h) and in the final (60 h) stages for LL and in the intermediary stages (45, 50 and 55 h) for LLc, indicating significant differences in the mechanisms of somite formation and development. Considering that both lines had the same genetic origin, such deviation indicates genetic changes due to artificial selection for body weight. The heritability estimates indicated low additive genetic effect for NOS in the different stages. Since the alterations were due to artificial selection for body weight, one could consider the hypothesis of using such genetic marker throughout family selection.